Association of thyroid function and obesity with chronic obstructive pulmonary disease: An observational cross-sectional study - Deepak Singh,; Anjuman Chaudhary,; Atul Kumar Singh,; Abhishek Singh, (Asian Journal of Medical Sciences, 2023)
Background: Chronic obstructive pulmonary disease (COPD), defined by GOLD as a preventable and treatable disease with some significant extra pulmonary effects, is a very common clinical entity in clinical practice. COPD is associated with significant extra pulmonary (systemic) effects. Systemic inflammation may be mainly driven by risk factor – cigarette smoking and it persists after smoking cessation. COPD is associated with severe extrapulmonary (systemic) manifestations and comorbidities such as cardiac, osteoporosis, gastroesophageal reflux disease, Thyroid Dysfunctions, and obesity. Body mass index (BMI) has also been identified as an independent prognostic factor for COPD. Aims and Objectives: This study was conducted to determine the proportion of hypothyroidism and obesity in COPD patients and their association with GOLD stage. Materials and Methods: This was an observational cross-sectional study assessing, COPD patients to determine proportions of thyroid disorder and obesity within a period of 1 year. Data were coded and recorded in MS Excel spreadsheet program. SPSS v23 (IBM Corp.) was used for data analysis. Results: The following variables were significantly associated (P<0.05) with the variable “GOLD Stage: Weight (kg), BMI, and obesity. 30 (35.3%) COPD patient having abnormal thyroid profile and all 30 (35.3%) were diagnosed as hypothyroid. Conclusion: From the study, it was found that BMI of patient decreases with increase in GOLD COPD staging. This indicates that obesity might have some protective effect in COPD but this need to be further evaluated.